Strategic people management: study of well-being at work in a furniture and electronics retail company (Research, Society and Development, 2023)
In contemporary times, “well-being at work” has been one of the most recurrent concerns of organizational psychology and people management professionals. The present work aims to analyze the level of “well-being at work” of the employees of a retailer of furniture and electronics, in a complementary way, aiming to develop proposals for intervention and improvement for the investigated company. For this purpose, we applied the Well-Being at Work Inventory (WBWI-13) to 11 employees of the company investigated. Using multilevel research and comprising the application of questionnaires and systematic observations, results show an average degree of well-being at work. In addition, we found that there is low identification of employees with the nature of work. Also, it lacks investment by the company to achieve the objectives of improving “well-being” in the work environment. Thus, we suggest (1) an investigation into the relationship between the nature of work and the vocation of employees; and (2) the creation of programs that emphasize the improvement of the quality of life.